SAMVC sistema de autoria de museus virtuais colaborativos - Schneider, Claúdio Alexandre (2011)
The use of graphical objects three-dimensional (3D) multimedia applications is gaining more space in the media. Networks with high transmission rates, computers with large processing and graphics boost and popularize such three-dimensional applications. The areas of 3D applications ranging from military applications, entertainment applications geared up for education. Within the applications related to education, we highlight the applications that create virtual copies of cultural spaces such as museums. Through this copy, you can virtually visit a museum, see other users, communicate, exchange information on works, etc. Thereby allowing the visit museums physically distant remote users. A major problem of such virtual environments is its update. By dealing with various media (text, images, sounds, and 3D models), its subsequent handling and update on a virtual environment requires staff with specialized knowledge. Speaking of museums, they hardly have people on your team with this profile. Inside the GT-MV (Grupo de Trabalho de Museus Virtuais), funded by RNP (Rede Nacional de Ensino e Pesquisa) propose a portal for registration, amendment and seen collaborative virtual museums of Brazil. The update, be it related to work or physical space, a system with a national scale like this, would be impossible if done only by the project team. Within this scenario, we propose the modeling and implementation of a tool that allows editing of virtual spaces in an easy and intuitive as compared with available tools. Within the context of GT-MV, we apply the SAMVC (Sistema de Autoria de Museus Virtuais Colaborativos) to museums where curators build the museum from a 3D floor plan (2D). The system, from these twodimensional information, recreates the equivalent in three dimensions. With this, through little or no training, team members from each museum may be responsible for updating the system